PENINGKATAN KINERJA PEGAWAI MELALUI PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA - Jumarti, Jumarti; Hamdyani, Sri; Rohani, Rohani (Jurnal Bisnis dan Kewirausahaan, 2024)
This study aims to analyze: (1) The Effect of HR Competency Development, including knowledge, skills, and attitudes towards employee performance partially and simultaneously, (2) The most dominant variables affect employee performance. This study used a quantitative approach, with a sample of 50 respondents, using saturated samples and multiple regression analysis. The results of hypothesis testing show: (1) Knowledge has a positive and significant effect on employee performance, (2) Skills have a positive and significant effect on employee performance, (3) Attitude has a positive and significant effect on employee performance, (4) Variables of knowledge, skills, attitudes simultaneously have a positive and significant effect simultaneously on employee performance, (5) The most dominant attitude variable affects the performance of